PENGEMBANGAN SOCIAL CAPITAL (MODAL SOSIAL) MELALUI OUTDOOR EDUCATION - Rikky Ridwan, - (2021)
ABSTRACT Rikky Ridwan * 1603043 Development Social Capital Through Outdoor Education Social capital will become stronger if in a society the norms of reciprocating mutual help and solid cooperation apply through a network of social institutional relationships.The Aim of this study was to determine whether there was an effect of the outdoor education program on the integration of social capital on the development of social capital. The experimental research method with pretest-posttest control group design with more than one experimental group was used in this study. This design was used because this study involved more than one experimental group. The results showed that outdoor education game programs arranged in a structured manner with a social capital integration process had significant results and effects on social capital development. Then, Coaches or staff can use these deliberately structured programs for the development of the affective aspect through various sports activities. Keywords: integration, outdoor education, social capital